Regulating role of abscisic acid on cadmium enrichment in ramie (Boehmeria nivea L.) - Kunmei Chen (Nature Portfolio, 2021)
Abstract Abscisic acid (ABA) is known as an important hormone regulating plant stress resistance, such as salt, drought and heavy metal resistance. However, the relationship between ABA and cadmium (Cd) enrichment in ramie (Boehmeria nivea L.) is still unclear to date. This study aimed to reveal the effect of ABA on Cd enrichment in ramie, and we received the following results: (1) Under Cd treatment, the Cd uptake of ramie increased with the increase of Cd concentration, but the chlorophyll content decreased. Under Cd treatment, the ABA content was highest in roots of ramie, followed by that in old leaves, and lowest in new leaves. Long-time treatment of high Cd concentration reduced the ability of endogenous ABA biosynthesis. (2) Spraying ABA on ramie plants (SORP) and adding ABA directly to the culture solution (ADCS) with low concentration can promote the growth of ramie and increase the amount of Cd uptake, and the effect of SORP is better. (3) The molecular reason for the decrease of chlorophyll content due to Cd stress, may be resulted from the down-regulated expression of the chlorophyll synthesis genes (BnPAO and BnNYC1) and the up-regulated expression of the chlorophyll degradation genes (BnCHLH, BnCHLG, BnHAP3A and BnPPR1). The elevated ABA content in ramie plants may due to the up-regulated expression of the ABA synthesis related genes (BnABA1, BnNCED3, and BnNCED5) and the genes (BnABCG40, BnNFXL2, BnPYL9, BnGCR2, BnGTG1, BnBGLU1, BnUTG1, BnVHAG1 and BnABI5) that encoding ABA transport and response proteins, which was consistent with the enhance the Cd uptake in ramie. Our study revealed the relationship between ABA and Cd uptake in ramie, which provided a reference for improving the enrichment of Cd in ramie.